2017
DOI: 10.1039/c6sc05581h
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-catalysed C–H carbonylative cyclisation of aliphatic amides

Abstract: A cobalt-catalysed C–H carbonylation of aliphatic carboxamide derivatives is described, employing commercially available Co(ii)-salts in the presence of a silver oxidant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(31 citation statements)
references
References 60 publications
1
28
0
2
Order By: Relevance
“…[103] Intermolecular amination can be achieved when aperfluorinated amide is added as anitrogen source.The Sundararaju [104] and Gaunt [105] research groups independently found that Co(acac) 2 catalyzes the carbonylative cyclization of amide 116 in the presence of carbon monoxide for access to succinimide 207. Scheme 37).…”
Section: Cobaltmentioning
confidence: 99%
“…[103] Intermolecular amination can be achieved when aperfluorinated amide is added as anitrogen source.The Sundararaju [104] and Gaunt [105] research groups independently found that Co(acac) 2 catalyzes the carbonylative cyclization of amide 116 in the presence of carbon monoxide for access to succinimide 207. Scheme 37).…”
Section: Cobaltmentioning
confidence: 99%
“…In 2017, Gaunt's group reported a cobalt-catalysed carbonylative cyclisation procedure of unactivated aliphatic C-H bonds (Scheme 55). [92] The key point of this methodology was the stabilizing effect of the quinolinamide directing group. The process tolerated a wide range of functionalized substrates to generate the corresponding substituted succinimide products.…”
Section: Scheme 54 Cobalt-catalysed C( Sp2 )−H Bond Carbonylation Ofmentioning
confidence: 99%
“…Li und Ge zeigten, dass das Amid 203 in Abwesenheit eines Alkins unter ähnlichen Reaktionsbedingungen eine b-Lactamisierung unter Bildung des b-Lactams 204 durchläuft. [103] Eine inter- [104] und Gaunt [105] stellten unabhängig voneinander fest, dass Co(acac) 2 [108] Nach dem postulierten Mechanismus bindet ein Nitronatligand über einen Ligandenaustausch an das Kupfer-(III)-alkyl H1,w odurch das Zwischenprodukt H2 entsteht. Eine reduktive Eliminierung führt zur Bildung einer C-CBindung und des Intermediats 210,d as weiter in das beobachtete cyclisierte Produkt 196 umgewandelt wird.…”
Section: Cobaltunclassified